Cloud security fears: fact or FUD?. (July 2015) - Ring, Tim
Abstract : The succession of warnings and reports of failings in cloud security, have had the inevitable effect of reinforcing many organisations' fears about moving into the cloud. But are people right to be so cautious? Cloud security has been branded as a significant issue, so it's not surprising that many enterprises remain reluctant to move their 'crown jewels' data into the cloud. But has the steady drip, drip of bad news made people too timid, meaning they miss out on the undoubted cost and efficiency benefits cloud adoption brings? Tim Ring reports on the still strong disagreements in the industry over cloud security but finds, behind the headlines, a growing consensus that – like it or not – cloud is the way to go.